Zad.1 Rozwiąż równania:
a) 3x-5=4+2x
b) 5x-17=-9x+3
c) 2x-4+5x=x+2
d) 7x+2=5+3x+9
e) -5x+10=-2x-8
f) 7x+14=5x-22
g) -3+2x-6=3-4x
h) -5x+12+x=2x-12
zad.2 Rozwiąż równania:
a) 2(x-3)+3(4-x)=5
b) 3(x-4)-2(2x-5)=-4
c) 2(x+4)-5(x+3)=2
d) -2(x+3)+4(2x+3)=-6
zad.3 Rozwiąż równania:
a) (4-2x)-(x+3)=(x-5)+(-3-x)
b) (3-2x)+(3x+4)=-(3-2x)+(5x+4)
c)-(x+3)+(2x-1)=(1+4x)+(3+x)
d)-(x+3)-(2x+8)=(-3-2x)+(2x+1)
zad.4 Rozwiąż równania:
a) (3-2x)-(x+4)-(2x+5)=(3x-4)-(5x+7)
b) (4-x)-(2x+3)+(x-4)=-(2x-3)-(x+7)
c) (4x-5)+(x-7)-(2x-8)=(-3x+4)-(x-6)
d) -(4-2x)-(2x+4)=(3x-1)+2x-5)-(7-3x)

2

Odpowiedzi

2010-03-13T11:37:23+01:00
Zad.1 Rozwiąż równania:
a) 3x-5=4+2x
x=9
b) 5x-17=-9x+3
14x=20
x=20/14=10/7=1i3/7
c) 2x-4+5x=x+2
6x=6 x=1
d) 7x+2=5+3x+9
4x=12 x=3
e) -5x+10=-2x-8
-3x=-18
x=6
f) 7x+14=5x-22
2x=-36
x=-18
g) -3+2x-6=3-4x
-2x=12
x=-6
h) -5x+12+x=2x-12
-6x=-24
x=4
zad.2 Rozwiąż równania:
a) 2(x-3)+3(4-x)=5
2x-6x+12-3x=5
-7x=-7
x=1
b) 3(x-4)-2(2x-5)=-4
3x-12-4x+10=4
-x=6
x=-6
c) 2(x+4)-5(x+3)=2
2x+8-5x-15=2
-3x=9
x=-3
d) -2(x+3)+4(2x+3)=-6
-2x-6+8x+12=-6
6x=-12
x=-2
zad.3 Rozwiąż równania:
a) (4-2x)-(x+3)=(x-5)+(-3-x)
4-2x-x-3=x-5-3-x
-3x=-9
x=3
b) (3-2x)+(3x+4)=-(3-2x)+(5x+4)
3-2x+3x+4=-3+2x+5x+4
-6x=-6
x=1
c)-(x+3)+(2x-1)=(1+4x)+(3+x)
-x-3+2x-1=1+4x+3+x
-4x=8
x=-2
d)-(x+3)-(2x+8)=(-3-2x)+(2x+1)
-x-3-2x-8=-3-2x+2x+1
-3x=9
x=-3
zad.4 Rozwiąż równania:
a) (3-2x)-(x+4)-(2x+5)=(3x-4)-(5x+7)
3-2x-x-4-2x-5=3x-4-5x-7
-3x=-5
x=5/3
b) (4-x)-(2x+3)+(x-4)=-(2x-3)-(x+7)
4-x-2x-3+x-4=-2x-3-x-7
3x=-1
x=-1/3

c) (4x-5)+(x-7)-(2x-8)=(-3x+4)-(x-6)
4x-5+x-7-2x+8=-3x+4-x+6
7x=14
x=2

d) -(4-2x)-(2x+4)=(3x-1)+2x-5)-(7-3x)
-2x=-5
x=5/2
3 3 3
Najlepsza Odpowiedź!
2010-03-13T11:37:31+01:00
Zad.1 Rozwiąż równania:
a) 3x-5=4+2x
x=9

b) 5x-17=-9x+3
14x=20
x=1 i 3/10

c) 2x-4+5x=x+2
6x=6
x=1

d) 7x+2=5+3x+9
4x=12
x=3

e) -5x+10=-2x-8
-3x=-18
x=6

f) 7x+14=5x-22
2x=-14
x=-7

g) -3+2x-6=3-4x
-2x=6
x=-3

h) -5x+12+x=2x-12
-2x=-24
x=12

zad.2 Rozwiąż równania:

a) 2(x-3)+3(4-x)=5
2x-6+12-3x=5
-x=-1
x=1

b) 3(x-4)-2(2x-5)=-4
3x-12-4x+10=-4
-x=-2
x=2

c) 2(x+4)-5(x+3)=2
2x+8-5x-15=2
-3x=9
x=-3

d) -2(x+3)+4(2x+3)=-6
-2x-6+8x+12=-6
6x=-12
x=-2

zad.3 Rozwiąż równania:

a) (4-2x)-(x+3)=(x-5)+(-3-x)
4-2x-x-3=x-5-3-x
-3x=-9
x=3

b) (3-2x)+(3x+4)=-(3-2x)+(5x+4)
3-2x+3x+4=-3+2x+5x+4
-7x=-8
x=1 i 1/7

c)-(x+3)+(2x-1)=(1+4x)+(3+x)
-x-3+2x-1=1+4x+3+x
-5x=8
x=-1 i 3/5

d)-(x+3)-(2x+8)=(-3-2x)+(2x+1)
-x-3-2x-8=-3-2x+2x+1
-3x=9
x=-3


zad.4 Rozwiąż równania:

a) (3-2x)-(x+4)-(2x+5)=(3x-4)-(5x+7)
3-2x-x-4-2x-5=3x-4-5x-7
-3x=-5
x=1 i 2/3

b) (4-x)-(2x+3)+(x-4)=-(2x-3)-(x+7)
4-x-2x-3+x-4=-2x+3-x-7
x=-1

c) (4x-5)+(x-7)-(2x-8)=(-3x+4)-(x-6)
4x-5+x-7-2x+8=-3x+4-6x+6
14x=14
x=1

d) -(4-2x)-(2x+4)=(3x-1)+2x-5)-(7-3x)
-4+2x-2x-4=3x-1+2x-5-7+3x
-8x=-5
x=5/8


POZDRo
:))
4 3 4